Perencanaan Pembelajaran dan Asesmen dalam Implementasi Kurikulum Merdeka di Sekolah Dasar - Jurdil, Rizky Roland; Hidayat, Otib Satibi; Jaya, Indra (Jayapangus Press, 2025)
The implementation of the Merdeka Curriculum in Indonesia has faced various challenges, particularly at the elementary school level. This study specifically aims to identify and describe the obstacles faced by teachers in designing learning plans and assessments that align with the Merdeka Curriculum. The research method used in this study is qualitative descriptive, involving two teachers from a public elementary school in Purwakarta Regency, West Java. Data was collected through semi-structured interviews and analysis of learning plan and assessment documents. The results showed that, in the context of learning planning, teachers have made efforts to understand the learning outcomes and design learning plans. However, there are several obstacles faced, such as the absence of learning outcomes for local content subjects, limited teacher understanding in the context of learning planning, and lack of time to complete teaching modules and learning goal pathways due to the demands of additional tasks. Meanwhile, in the context of assessment planning, teachers tend to rely on existing sources, both from teaching modules and textbooks. These findings indicate that although teachers have made efforts to design learning and assessment plans, there are still gaps in understanding and practice. This indicates the need for more intensive support for teachers in terms of capacity development, especially in designing learning plans and assessments that meet the needs of students.